Current and frequency control of induction generator : simulation using MATLAB - Taufik, Mohd Nor (2010)
Induction machine is the most widely used machine nowadays in industry and generation systems. It haves two mains types that usually use, squirrel cage and wound type. This project is about the control of current and frequency of wound rotor induction generator in wind turbine generation system. By controlling the current and frequency at the rotor of the generator, the active and reactive power produce by the generator can be regulate and maximize the generator performance. To control the current and frequency of induction generator in wind turbine application, this project uses an AC/DC/AC converter that directly connected to rotor. AC/DC/AC converter is a bi-directional converter that enables the generator to operate above and below the synchronous speed thus allow the generator to generate and absorb power from the grid. This system is called Doubly Fed Induction Generator (DFIG) in wind turbine application system where the stator is directly connected to grid and the rotor is connected to grid via AC/DC/AC converter. This project use MATLAB software to simulate the system and analyze the result obtains from the simulation. From the result, it shows that this system is function successfully and the objective is achieved.